Televisual forensics on the edge of chaos: postgenomic complexity in CSI: Crime Scene Investigation. (11th March 2015) - Bull, Sofia
Abstract : This essay examines the discourse on scientific knowledge in the forensic crime drama CSI: Crime Scene Investigation (CBS, 2000–), in ways that complicate the common assumption that its science only offers conservatively straightforward answers and simple solutions. Through close textual readings, and comparative historic genre analysis of The Expert (BBC, 1968–76), Quincy M.E. (NBC, 1976–83) and Silent Witness (BBC, 1996), the essay maps the residual, dominant and emergent scientific discourses in CSI . It is argued that the programme simultaneously engages with traditional biological frameworks, investments in essentialist and determinist genetics, and a newly emergent postgenomic structure of feeling that expresses an amplified sense of complexity and indeterminacy, presumably produced by an increasingly perceptive scientific gaze. The analysis closely examines CSI 's traditional depiction of science as a visual practice and its new dynamic use of microscopic imagery; its formulaic episodic format and unusual use of uncertain flashbacks; as well as its perhaps surprising tendency to feature plotlines about random deaths. By thus considering the series' generic formal conclusions, as well as its innovative elements, the multiplicity of CSI 's discourse on science becomes more apparent. The essay concludes that scientific order is depicted as existing 'on the edge of chaos': at least momentarily articulating the impossibility of complete certainty and order.